2010
DOI: 10.1590/s0004-282x2010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disorders in children of a public hospital in São Paulo

Abstract: Objective: To investigate the prevalence of sleep disorders in a sample of children from a public hospital in the city of São Paulo, Brazil. Method: 330 children, who came to the clinical laboratory, were consecutively investigated for sleep disorders, using the sleep disturbance scale for children. Gender, age, and social/economical classification were considered. Results: Sleep disordered breathing (SDB) showed higher prevalence in our sample (55%) than in data found in the literature. Prevalence of sleep hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
(43 reference statements)
0
2
0
1
Order By: Relevance
“…The majority of studies using the SDSC scale have identified an association between sleep breathing disorders and pathological conditions, a finding replicated in our HIVinfected population. In a study involving Brazilian children, a prevalence of sleep breathing disorders of 55% was found in a population seen at a clinical laboratory of a public pediatric hospital 21 . This prevalence was considered high compared to the international literature, a finding speculatively attributed by the authors to respiratory diseases secondary to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies using the SDSC scale have identified an association between sleep breathing disorders and pathological conditions, a finding replicated in our HIVinfected population. In a study involving Brazilian children, a prevalence of sleep breathing disorders of 55% was found in a population seen at a clinical laboratory of a public pediatric hospital 21 . This prevalence was considered high compared to the international literature, a finding speculatively attributed by the authors to respiratory diseases secondary to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…As to Brazil, the role of free universal access to treatment and integral care is noteworthy, including instruments of social support 9 . With regard to healthy adolescents, a number of recent studies carried out in Brazil have shown high prevalence of sleep disturbances in children and adolescents, associated with both clinical aspects and lifestyle, such as poor sleep hygiene and sleep deprivation 12,13,21 . Additionally, the adolescents in the Control Group, drawn from users of public schools in large urban centers, had very similar social indicators to those infected by HIV, which could reflect comparable living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo realizado com escolares de um município da Paraíba, identificou-se a prevalência de DRS (10%) e HS (15%) na população analisada (Souza & Tomaz, 2017), diante destes dados, pesquisa realizada com crianças paulistas identificou a presença de DRS e HS, sendo o DRS mais preponderante (Potasz et al, 2010). No presente estudo, a DRS também foi o distúrbio de sono mais frequente entre os participantes e a HS o menos prevalente.…”
Section: Discussionunclassified